I2-Catalyzed Access to Bis(pyrazolo[1,5-a]pyrimidinyl)sulfanes and Sulfenylated Pyrazolo[1,5-a]pyrimidines via C-H Functionalization - Choudhuri, Tathagata; Sikdar, Papiya; Paul, Suvam; Das, Sourav; Bagdi, Avik Kumar (Synlett)
We have demonstrated a new route to bis(pyrazolo[1,5-a]pyrimidinyl)sulfanes from pyrazolo[1,5-a]pyrimidines through I2-catalyzed C-H functionalization employing thiourea as the sulfur source. 3-Iodopyrazolo[1,5-a]pyrimidines acted as the active intermediates for this radical C-H sulfenylation. This I2-catalyzed C-H sulfenylation has been extended towards the synthesis of sulfenylated pyrazolo[1,5-a]pyrimidines using sulfonyl hydrazides as sulfenylating agents. Various bis(pyrazolo[1,5-a]pyrimidinyl)sulfanes and sulfenylated pyrazolo[1,5-a]pyrimidines have been synthesized using these simple protocols. The use of easily accessible and bench-stable reactants and reagents, metal-free catalysis, broad substrate scopes, and practicality are the attractive features of this strategy. Moreover, the usefulness of thiourea as a sulfur source in the synthesis of bis(2-phenylimidazo[1,2-a]pyridin-3-yl)sulfane and bis(6-phenylimidazo[2,1-b]thiazol-5-yl)sulfane derivatives has been demonstrated.